The IOP lowering effects of “planning” selective laser trabeculoplasty in open angle glaucoma - Chu, Yi-Ching; Chang, Pei-Yao; Wang, Jia-Kang; Huang, Tzu-Lun; Hsu, Yung-Ray (Frontiers in Medicine, 2022)
Purpose: To investigate whether the planning of selective laser trabeculoplasty (SLT) influences the intraocular pressure (IOP) in patients with open angle glaucoma (OAG). Methods: In this retrospective case-control study conducted on patients with OAG who planned to undergo SLT treatment (SLT group) or a visual field examination (VF group), we collected the demographic data, IOP on the planning day and on the scheduled day of the SLT treatment or VF examination. ΔIOP was defined as the IOP change between the planning day and the scheduled day. We used multivariable regression analyses and linear mixed model to evaluate the association between the abovementioned factors and ΔIOP in the VF group and the treatment eye (SLTt) and fellow eye (SLTf) of the SLT group. Results: 153 eyes of 102 patients with OAG were included, of which 51 patients in the SLT group and 51 patients in the VF group. The ΔIOP was -1.92±2.77 mmHg in the SLTt, -0.65±2.47 mmHg in the SLTf and -0.08±1.73 mmHg in the VF group (P<0.05). Both multivariable regression analysis between the VF and SLTt group and linear mixed model in the SLT group showed significant negative association between the ΔIOP and SLT arrangement (P<0.05). There was no significant association between ΔIOP and age, gender, baseline IOP, IOP fluctuation, nor SE. Conclusions: The IOP was significantly reduced in patients with OAG after “planning” of SLT treatment, even without actual performing the laser treatment in our retrospective case-control study.